MON-540 Familial Hypocalciuric Hypercalcemia Diagnosed in a 63-Year-Old Female - Mudgal, Mayuri (J Endocr Soc, 2019)
Background Familial Hypocalciuric Hypercalcemia (FHH) is a rare autosomal dominant genetic disorder which causes impaired calcium sensing receptor (CaSR) function which is located in the parathyroid and kidneys. This disorder leads to hypercalcemia, hypocalciuria and normal to moderately elevated parathyroid hormone (PTH). Here we present a case of asymptomatic FHH diagnosed in the seventh decade of life. Case description A 63-year old Caucasian female was referred to the endocrinology clinic for evaluation of her hypercalcemia. Patient had elevated blood calcium levels (ranging from 10.5-11 mg/dl) since the age of 55. She denied any history of kidney stones, osteoporosis, fracture or malignancy. There was no family history of hypercalcemia. Her other medical history included diabetes mellitus type 2, hypertension, hyperlipidemia and depression. Medications were Metformin, insulin, enalapril, simvastatin, fluoxetine. Laboratory workup revealed calcium 10.1mg/dl, PTH 77.3 pg/ml, 25 OH Vit D 22 ng/ml, Initial urine 24-hour calcium 0mg/24 hr, creatinine 1.2 mg/dl, 24-hour urine creatinine 1.1 mg/dl. DEXA scan with normal bone mineral density. Vitamin D was supplemented and subsequent repeat urine 24-hour calcium had improved but was still low at 29mg/24 hour with urine calcium/creatinine ratio of 0.029. Follow-up blood calcium levels showed fluctuations ranging from 9.4-10.3. Patient was subsequently referred for genetic testing which returned positive for heterozygous mutation in the CASR gene. Discussion FHH is an inherited disorder with prevalence of 1 in 78,000 and presents as benign, lifelong, persistent hypercalcemia and hypocalciuria without hypercalcemic related complications. Patients are mostly asymptomatic but there have been cases of pancreatitis, gall stones and chondrocalcinosis noted in literature from FHH. Conclusion Distinguishing FHH from primary hyperparathyroidism is important as the former is benign and does not require any surgical intervention while latter is cured with parathyroidectomy. This case identifies the role of primary care physicians in timely detection of hypercalcemia and subsequent diagnosis which can prevent unnecessary parathyroid surgical procedures as well as complications from hypercalcemia in patients with primary hyperparathyroidism.